The CO2 emission Gini index and the environmental efficiency: An analysis for 60 leading world economies - Thiago Costa Soares; Elaine Aparecida Fernandes; Silvia Harumi Toyoshima (EconomiA, 2018)
The aim of this study was to analyze the CO2 emission Gini index and the environmental efficiency for 60 leading world economies, in 2010. We consider the technological heterogeneity dividing the sample into similar groups, and estimating environmental efficiency indicators into metafrontier and group frontiers. Despite the fact that pollution concentration is more prominent in developed countries, the results showed that this group is more efficient. On the other hand, lower-income group, and medium-technology countries present the worst indicators. We could conclude that the inefficiency observed in developed countries group was attributed to mismanagement, while in the developing countries group the inefficiency could be related to technological differences.
Keywords: C61; O57; Q54; 330; Environmental efficiency; Gini index; Metafrontier; Pollutants